DAYA SAING DAN FAKTOR YANG MEMPENGARUHI EKSPOR LADA INDONESIA KE AMERIKA: PENDEKATAN REVEALED COMPARATIVE ADVANTAGE - Maria Nina Egyna Brahmana; Tanti Novianti (University of Jember, 2022)
The US was the world's largest pepper importer in 2020. Most of the US pepper imports came from Indonesia and Vietnam. The greater the number of imports will lead to the emergence of many competitors from other countries. The increasing producers and exporters of a product worldwide will result in tighter competitiveness between countries to win the market. Indonesian pepper exports fluctuate and tend to decrease, allegedly due to the low competitiveness of Indonesian pepper products compared to Vietnam. This study aims to analyze the competitiveness of Indonesian and Vietnam black pepper and analyze factors that affect Indonesian black pepper exports to America. This research is a quantitative research that uses secondary time series data from the period 2011-2020. Data sources were obtained from UN Comtrade, Central Statistics Agency, Ministry of Agriculture, and Indonesia Central Bank. The analysis uses RCA and Multiple Regression. The results showed that Indonesian pepper export competitiveness has an RCA value of 25.83, and Vietnam has RCA of 29.28. The volume of exports made by Indonesia to the American market is markedly influenced by the value of RCA and exchange rates, while the price of exports and domestic pepper production has no significant effect.